Accountability And Internal Control Systems On The Quality Of Regional Equipment Organizational Reports With Organizational Commitment As Moderation - Saputra, Bagaskara Aji; Gunawan, Barbara (Journal of Multiperspectives on Accounting Literature, 2023)
Purpose: This study aims to examine the effect of accountability and internal control systems on thequalityof financial reports of regional apparatus organizations with organizational commitment as moderation. Methodology/approach: Collecting data in this study using a questionnaire. Questionnaires were distributed as many as 120 questionnaires which were distributed to 20 OPD in Bantul Regency. A total of 95 questionnaires were filled out and returned to the authors for analysis. This research is included into quantitative research. The sample in this study used purposive sampling. The analytical tool used in this study is multiple linear regression with the IBM SPSS Statistics 22 application. Findings: The results of this study indicate that accountability has a positive and significant effect on the quality of financial statements of local government organizations, the internal control system has a positive effect on the quality of financial reports and the internal control system has a positive and significant effect on the quality of financial reports and is moderated by organizational commitment. Practical implications: Future will improve accountability performance of a government agency so that the government can provide information to the public in the form of quality financial reports. Originality/value: Accountability has a role to describe the success or failure of an organization's mission to achieve predetermined goals and indicators in the form of local government financial reports.